Evaluation of bronchial hyperresponsiveness in asthmatic paediatric patients using mannitol challenge test – Impacts of body mass index - Sharon S. Y. Leung; Helen S. L. Tsang; Jasmine Chan; Oliver Y. H. Kui; Ping Zeng; Yin Ting Cheung; James-Wesley Cheng; Kate C. C. Chan; Michelle Yu; Patricia Tang; John D. Brannan; Jenny K. W. Lam; et al. (Annals of Medicine)
Background Increasing epidemiological studies reported that overweight/obese asthma patients had more frequent and severe symptoms and exacerbations, indicating their asthma management may not be sufficient. Airway hyperresponsiveness (AHR), a significant feature of asthma, was found to link with the body mass index (BMI) with mixed findings using the “direct” methacholine challenge test. The objective was to examine the association between BMI and asthma control, as reflected by the “indirect” AHR with the mannitol challenge test in a paediatric asthmatic population.Methods A total of 80 subjects with physician-diagnosed asthma, aged 6–18 years were enrolled in this cross-sectional study. Patients were first asked to complete the Asthma Control Test (ACT) questionnaire to self-evaluate their disease status. A mannitol challenge test was then performed to assess their AHR severity.Results Seventy-six patients (96%) rated their asthma as well-controlled with an ACT score ≥ 20, but 42 patients (53%) were tested positive in the mannitol challenge test with mild and moderate AHR. While patients with mild AHR had comparable lung functions to those without AHR, patients with moderate AHR showed slightly but significantly lower FEV1 and FEV1/FVC values. Although no significant difference in the BMI values was noted for patients with different levels of AHR, the trend of increasing BMI with age was steeper for patients with moderate AHR.Conclusion A high prevalence of AHR (>50%) was found in asthmatic children who self-evaluated with good asthma control. No significant influence of the BMI on the AHR severity could be demonstrated in this population with the “indirect” mannitol challenge test. Since only a small number of overweight/obese subjects were recruited in the present study, further verification of the results with a larger sample size of obese subjects is required.